Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.bmcl.2016.03.100
|View full text |Cite
|
Sign up to set email alerts
|

Anilinoquinazoline inhibitors of the RET kinase domain—Elaboration of the 7-position

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The key to increased selectivity compared to vandetanib was a change in substituents around the phenyl ring, which also led to improved metabolic and pharmacokinetic features . This family was further elaborated in a more recent work, where the authors identified compounds with improved cellular selectivity (Jordan et al 2016).…”
Section: Next Generation Of Ret Targeted Drugsmentioning
confidence: 99%
“…The key to increased selectivity compared to vandetanib was a change in substituents around the phenyl ring, which also led to improved metabolic and pharmacokinetic features . This family was further elaborated in a more recent work, where the authors identified compounds with improved cellular selectivity (Jordan et al 2016).…”
Section: Next Generation Of Ret Targeted Drugsmentioning
confidence: 99%
“…A collection of 42 anilinoquinazoline derivatives as RET kinase antagonists were taken for the study . Converted pIC 50 values (−log IC 50 ) from the reported IC 50 values (μM) of the compounds shows the log span of 3.7 which is satisfactory to perform a 3D‐QSAR study .…”
Section: Methodsmentioning
confidence: 97%
“…Recently FDA and EMA have approved vandetanib, cabozantinib, sorafenib, and lenvatinib for the treatment of MTC. But, these inhibitors are non‐selective to RET and possess elevated efficacy against some other protein kinases . These drugs are also ineffective inhibitors against the gatekeeper mutants V804M and V804L .…”
Section: Introductionmentioning
confidence: 99%
“…Within the organizations collaborating in this work and in those who have been able to exploit the data in trial form in universities and not for profit organizations, the knowledge has contributed to solving a number of drug hunting project problems leading to several publications . [40][41][42] We have also shown examples of transformations that run counter to established wisdom. These may be useful tools to extricate a drug hunting team from a tight optimization corner and more generally to provide opportunities to enhance our understanding of the general SAR of the system being studied.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%